Familial Exudative Vitreoretinopathy: Follow-Up and Treatment Results - Zafer Cebeci; Dilbade Yıldız Ekinci; Şerife Bayraktar; Nur Kır (Türk Oftalmoloji Dergisi, 2014)
Objectives: To report the follow-up and treatment results of cases with the diagnosis of familial exudative vitreoretinopathy (FEVR) in our clinic. Materials and Methods: We retrospectively reviewed the records of 19 eyes of 10 cases of FEVR that were followed up and some of them were treated in our clinic. Results: Nine male and one female patients with a mean age of 10.1 (3-30) years were included in the study. Seven patients had a family history of FEVR. Twelve eyes of 8 patients had laser photocoagulation to peripheral avascular areas, 3 patients had vitreoretinal surgery on one of their eyes three times. Unilateral total retinal detachment was determined in two patients at the initial visit and in three patients at the follow-up visits; because no improvement in the vision was expected, surgery was not done. Conclusion: FEVR is an inherited disease that can be detected in any age and can cause severe vision loss. These patients should be followed up throughout the life, and the essential treatment at the appropriate time can lead to partial visual recovery. (Turk J Ophthalmol 2014; 44: 370-3)